Politeness Strategies in 2014 Presidential Debates between Joko Widodo and Prabowo Subianto - Marischa Dwi Fergina and Sri Juriati Ownie (LINGUISTICA, 2015)
This study analyzed the politeness strategies employed by Joko Widodo andPrabowo Subianto in 2014 Presidential Debates. This study used descriptivequalitative method. Kothari (2004:2) states that Descriptive research includessurveys and fact-finding enquiries of different kinds. In this study the writerdescribed the utterances of president candidates debate into written text. Themajor purpose of descriptive research is description of the state of affairs as itexists at present. The instrument of collecting data is video recording of DebatCapres Cawapres Jokowi Jk- Prabowo Hatta at Metro TV on July 5, 2014.Particular attention is given to candidate’s use of bald on record, positivepoliteness, negative politeness, off record and do not do speech act or do the FTA(face threatening act) as defined by Brown and Levinson theory. The focus of thepaper is on the types of politeness strategies that used in debate, the dominant typeof politeness strategies, and the reason of dominant type usage in debate. Theresult showed that the most dominant type is Positive politeness (61,53%). Thenthere was also Negative politeness (30,76%), On record (3,84%), Off record(3,84%) and do not do the FTA (0%). The president candidates mostly usedpositive politeness because want to reduce face-threatening act besides how thetwo candidates can be conveyed smoothly without making one party feelsthreatened.